A new genus and three new species of Pterostichini (Coleoptera: Carabidae) from Mêdog, China - Wang, Ya-Nan; Shi, Hong-Liang; Liang, Hong-Bin (Zootaxa, 2026)
This study deals with the taxonomy of the tribe Pterostichini (Coleoptera: Carabidae) from Mêdog County, Xizang, China, where we describe one new genus, Medogia Wang & Shi gen. nov. (type species: Medogia mirabilis sp. nov.), and three new species: Medogia mirabilis Wang & Shi sp. nov. (type locality: Mêdog, 62K, 2794 m), Medogia melanaria Shi & Wang sp. nov. (type locality: Mêdog, Lage, 3270 m), and Pterostichus (Circinatus) medogensis Shi & Wang sp. nov. (type locality: Mêdog, 62K, 2794 m). To verify the establishment of the new genus, a preliminary phylogenetic analysis based on molecular data was conducted. As a result of this study, the Pterostichini fauna of Mêdog County comprises eight species, categorized as follows: three new species described herein, two species newly recorded from the county [Pterostichus (Pseudethira) rugosiceps Schmidt, 2012 and Nirmala odelli Andrewes, 1930], and three previously recorded species. Additionally, the male genitalia of P. rugosiceps are described and illustrated for the first time.